Dampak pilihan fasilitas pada pola pembelanjaan Wisata ice :: Kasus di Jakarta Convention Center Jakarta - ABDULLAH, M. Razi ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Beside Bali, Jakarta now has become one of popular MICE tourism destinations in Indonesia. MICE is one of business in tourism industries which is seen as a big potential especially from economic side and its wide impact spectrum. In relation to that situation, the study tries to analyze the aspects of MICE which are related to shopping patterns and the choices of facilities provided. The case taken is Jakarta Convention Center (JCC). Subjects analyzed are delegations attending MICE in JCC. Based on the observation it was found out that there was an influence between the availability of facilities toward MICE tourism spending patterns. The influence existed because of several reasons. First, the nearness venue of the event to the other facilities (shopping arcade, tourism object, entertainment centers, sport center, culinary, etc). Second, kinds of facilities that were used of chosen (starred hotels/non starred hotels, entertainment center, eating place, sport facilities, shopping center, etc). Third, the varieties and the quality of the facilities provided (varieties of hotels, varieties of eating places, varieties of sport centers, varieties of recreational facilities). Accomodation facilities became the highest shopping component. It happened because the options were starred-hotels which are relatively expensive. The nearness of venue had an effect toward shopping motivation in the art shop facilities/souvenir shopping palces. Souvenirs became an important factor for the exhibition group, but no for conference group. Entertainment facilities generally was not considered important, however, the expenses for this facilities component wre high especially for exhibition group. Tourism attractions/shopping for recreation facilities were the most popular. Shopping activities were relatively in high level and the venue nearness factor was the motivation to do shopping activities. For the sport facilities, only conference group liked sport facilities, but exhibition group did not. Golf was the sport that was liked – a sport which relatively expensive. In culinary factor, spending pattern was more influenced by the delegations motivation to enjoy food especially at malls. For culinary or sport facilities there weren’t any specific differences between conference tourists or exhibition tourists.